Rudolf Bultmann - Ashcraft, Morris (Makers of the modern theological mind, 2016)
1. Rudolf Bultmann -- 2. Bultmann's understanding of man - the concept of existence -- 3. Bultmann's understanding of history -- 4. Bultmann and the historical Jesus -- 5 Demythologizing - existentialist interpretation -- 6. Existential speaking 'of' God -- 7. Ground of faith - the Christ event -- 8. Existence prior to faith - inauthentic existence -- 9. Life in faith - authentic existence -- 10. Summary and evaluation.